Numerical calculation and experimental verification of the fictitious angular velocity for transient temperature impact on the fiber-optic gyroscope coil - Esipenko, Ivan Aleksandrovich; Lykov, Daniil Andreevich (Computational Continuum Mechanics, 2017)
Numerical simulation and experimental investigation of the effect of two types of quadrupole winding of fiber coil on the fictitious angular velocity of a fiber-optic gyroscope under transient temperature conditions are carried out. The coil is formed by winding optical fiber precovered with two protective-hardening layers on the cylindrical surface and its further fixation by compound. For experimental verification of the fictitious angular velocity, a special device was made, in which the fiber coil was held by rubber gaskets used to maximally exclude the transfer of mechanical loads from the body parts to the coil. A functional for the fictitious angular velocity is represented as a function of temperature and elastic strain rate in the fiber core. In the software ANSYS, a two-dimensional axisymmetric finite-element analog of a structurally inhomogeneous coil in the device is modeled. To verify the elastic strains under uniform thermal actions, the problem of stationary thermoelasticity was solved. With the Brillouin optical time domain analyizer, Brillouin frequencies shifts at two temperatures were established, and the distribution of strains was obtained. A comparison of the calculated and experimental strains made it possible to refine the Poisson’s ratio of a weakly compressible primary coating. The solution of the transient thermal problem and temperature sensor readings allowed us to establish the heat-conductivity coefficient between the device and the moving air in the heat chamber. As an impact, we considered the heating of the environment at a rate of 1 °C/min, followed by a steady-state output. To find the temperature and strain fields for the functional of fictitious angular velocity, the unbound quasistationary thermoelasticity problem was solved. Tests were carried out with two types of winding of the coil. The experimental results showed satisfactory agreement with the calculated data.